THU0563 The immunomodulation effect of bm-mscs on the inflammatory chemokines of rats with collagen type ii induced arthritis. (15th June 2017) - Fan, J; Zhang, L; Ma, D; Zhang, G; Xu, K; Gao, J
Abstract : Background: Rheumatoid arthritis (RA) is an autoimunme disease.The DMARDs is mian treatment but side effects are very high. Bone marrow mesenchymal stem cells (MSCs) have immunoregulatory function so it can be used to treat RA. This study was designed to investigate the effect of BMSCs on chemokines in CIA rats. Objectives: To observe the immunomodulation effects of BM-MSCs on the Inflammatory Chemokines of rats with collagen-induced arthritis (CIA). Methods: Rats MSCs were isolated and expanded from bone marrow cells by density gradient centrifugation and adhering to the culture plastic bottle, and the phenotypes were assessed by flow cytometry. We established collagen induced arthritis rats model. A total of six groups. The MSCs treatment groups contain the early and advanced stages. Meanwhile, there are normal control and CIA control group, The latter also contains the early and advanced stages. Also, there is the positive control group of MTX, by intraperitoneal injection of a small dose of MTX (0.9mg/kg/w), for six weeks. 1x10 6 /kg BM-MSCs were implanted through tail vein to MSCs treatment groups, model control groups with equal amounts of saline served as controls.At forty two day, stream multi-factor detection technique were used to detect the level of RANTES, MCP-1 and IP-10 in serum of CIA rats. Results: The level of RANTES, AMCP-1, AIP-10 was higher in CIA control group than normal group (P<0.05); After MTX treatment, these factors level were significantly difference than the CIA control group (P<0.05). These factors level were lower in early BMSCs treatment groups than early CIA control groups (P<0.05), while the late MSCs treatment group versus the later CIA control group showed no statistically significant difference (P>0.05). The early and late MSCs treatment group versus the MTX treatment group showed no statistically significant difference (P>0.05). Conclusions: In this study MSCs has shown significant immune modulatory effects. It down regulates the level of Inflammatory Chemokines in CIA rats. The early treatment group is more effective than the late treatment group. References: Stuad JM, Cremer MA, Townes AS, et a1.Type lI collagen induced arthritis in rats: passive transfer with serum and evidence that IgG antieollagen antibodies can cause arthritis.J Exp Med, 1982, 155:l-16. Brahn E, Peacock DJ, Banquerigo ML. Suppression of collagen-induced arthritis by combination cyclosporin A and methotrexate therapy. Arthritis Rheum.1998, 34 (10):1282–1288. Dominici M, Le Blanc K, Mueller I, et al. Minimal criteria for defining multipotent mesenchymal stromal cells. The International Society for Cellular Therapy position statement. Cytotherapy. 2006;8(4):315–317. Park MJ, Kwok SK, Lee SH, et al.Adipose tissue-derived mesenchymal stem cells induce expansion of Interleukin-10 producing regulatory B cells and ameliorate autoimmunity in a murine model of systemic lupus erythematosus.Cho Cell Transplant. 2014 Dec 12. [Epub ahead of print]. Kehoe O, Cartwright A, Askari A, et al.Intra-articular injection of mesenchymal stem cells leads to reduced inflammation and cartilage damage in murine antigen-induced arthritis. J Transl Med. 2014, 12:157. Acknowledgements: Mesenchymal stem cell;Arthritis, rheumatoid; Collagen II induced arthritis (CIA);Inflammatory chemokine. Disclosure of Interest: None declared